Trial-by-trial modulations in the orienting of attention elicited by gaze and arrow cues. Issue 3 (March 2019) - Ciardo, Francesca; Ricciardelli, Paola; Iani, Cristina
Recent findings suggested that the orienting of attention towards gazed at locations (i.e., the gaze cueing effect) could result from the conflict emerging in incongruent trials between the spatial information conveyed by gaze direction and the target spatial position. In two experiments, we assessed this hypothesis by investigating whether this effect is influenced by the same trial-by-trial modulations that are reported in a spatial conflict task, i.e., the Simon task. In Experiment 1, we compared the trial-by-trial modulations emerging in the Simon task with those emerging in a gaze cueing task, while in Experiment 2, we compared gaze and arrows cues. Trial-by-trial modulations were evident in both tasks. In the Simon task, correspondence sequence affected both corresponding and noncorresponding responses, this resulting in a larger Simon effect when the preceding trial was corresponding and an absent effect when the preceding trial was noncorresponding. Differently, in the gaze cueing task, congruence sequence affected only congruent responses with faster responses when the preceding trial was congruent compared to when it was incongruent, resulting in a larger gaze cuing effect when the preceding trial was congruent. Same results were evident with nonpredictive arrow cues. These findings speak against a spatial conflict account.